2014
DOI: 10.1051/0004-6361/201323043
|View full text |Cite
|
Sign up to set email alerts
|

Sizes of protoplanetary discs after star-disc encounters

Abstract: Most stars do not form in isolation, but as part of a star cluster or association. These young stars are initially surrounded by protoplanetary discs. In these cluster environments tidal interactions with other cluster members can alter the disc properties. Besides the disc frequency, its mass, angular momentum, and energy, the disc's size is particularly prone to being changed by a passing star. So far the change in disc size has only been investigated for a small number of very specific encounters. Several s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
140
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 73 publications
(152 citation statements)
references
References 34 publications
(78 reference statements)
6
140
1
Order By: Relevance
“…They performed simulations of isolated star-disc encounters for a wide range of periastron distances and mass ratios, choosing the highest contrast in surface density to determine the disc sizes after the encounters. This is similar to the criterion used by observations, and the results by Breslau et al (2014) can easily be applied to cluster simulations. They showed that encounters with large periastron distances and/or low mass ratios do not remove material from the disc but shift it inwards, reducing the disc size but not the mass.…”
Section: Introductionmentioning
confidence: 75%
See 3 more Smart Citations
“…They performed simulations of isolated star-disc encounters for a wide range of periastron distances and mass ratios, choosing the highest contrast in surface density to determine the disc sizes after the encounters. This is similar to the criterion used by observations, and the results by Breslau et al (2014) can easily be applied to cluster simulations. They showed that encounters with large periastron distances and/or low mass ratios do not remove material from the disc but shift it inwards, reducing the disc size but not the mass.…”
Section: Introductionmentioning
confidence: 75%
“…Third, the discs were modelled consisting of mass-less tracer particles and hydrodynamical effects were excluded, for an indepth discussion see Breslau et al (2014). Rosotti et al (2014) found that the hydrodynamical evolution of the discs is important for high viscosity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…3, we discussed the possibility that a stellar fly-by could have stabilized the planet mid-ejection. The effect of such encounters on a disk has been studied intensively (for example in Breslau et al 2014;Jílková et al 2016). This effect is of course very dependent on the mass ratio of the stars and on the encounter periastron and eccentricity.…”
Section: The Effect Of a Stellar Encountermentioning
confidence: 99%